1979
DOI: 10.1192/bjp.134.5.488
|View full text |Cite
|
Sign up to set email alerts
|

Finger Tremor and Extrapyramidal Side Effects of Neuroleptic Drugs

Abstract: Finger tremor and extrapyramidal side-effects (EPSEs) were measured in seven patients before and during neuroleptic drug treatment to assess the relationship between the onset of EPSEs and changes in finger tremor spectra. Tremor and EPSEs were also measured in twelve patients stabilized on neuroleptic drugs to determine whether tremor could provide a reliable index of the presence and severity of extrapyramidal system disturbance. A downward shift in peak tremor frequently was noted within 48 hours of startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This involves the measurement of finger tremor using a piezoelectric accelerometer with computerised power spectral analysis (Collins, Lee & Tyrer, 1979) , it has to be acknowledged that at the present time the structured methods available for assessing extrapyramidal disorder are not well developed (Mindham, 1976).…”
Section: Assessing Extra-pyramidal Complicationsmentioning
confidence: 99%
“…This involves the measurement of finger tremor using a piezoelectric accelerometer with computerised power spectral analysis (Collins, Lee & Tyrer, 1979) , it has to be acknowledged that at the present time the structured methods available for assessing extrapyramidal disorder are not well developed (Mindham, 1976).…”
Section: Assessing Extra-pyramidal Complicationsmentioning
confidence: 99%
“…A recent and technically sophisticated refinement seeks to quantify objectively the earliest signs of druginduced Parkinsonism. This involves the measurement of finger tremor using a piezoelectric accelerometer with computerised power spectral analysis (Collins, Lee & Tyrer, 1979)). The authors have demonstrated that clinical signs of extrapyramidal impairment correlate closely with a reduction in the frequency of finger tremor from the physiological range (10 Hz) to the Parkinsonian range (5)(6).…”
Section: Assessing Extra-pyramidal Complicationsmentioning
confidence: 99%
“…The authors have demonstrated that clinical signs of extrapyramidal impairment correlate closely with a reduction in the frequency of finger tremor from the physiological range (10 Hz) to the Parkinsonian range (5)(6). Of particular interest is the finding that the frequency shift precedes the emergence of clinically detectable signs and so may represent a sensitive predictor of extrapyramidal disorder in the course of drug-treatment (Collins et al, 1979). However, validity remains an open question and it is hardly a technique which recommends itself by its simplicity.…”
Section: Assessing Extra-pyramidal Complicationsmentioning
confidence: 99%